Targeting oxidative stress for the treatment of ischemic stroke: Upstream and downstream therapeutic strategies - Wenjun Li; Shaohua Yang (Brain Circulation, 2016)
Excessive oxygen and its chemical derivatives, namely reactive oxygen species (ROS), produce oxidative stress that has been known to lead to cell injury in ischemic stroke. ROS can damage macromolecules such as proteins and lipids and leads to cell autophagy, apoptosis, and necrosis to the cells. This review describes studies on the generation of ROS, its role in the pathogenesis of ischemic stroke, and recent development in therapeutic strategies in reducing oxidative stress after ischemic stroke.